Double object constructions and dative / accusative alternations in Spanish and Catalan: A unified account - Pineda, Anna (Borealis – An International Journal of Hispanic Linguistics, 2013)
This paper has a twofold aim: to present a unified analysis of ditransitive constructions and transitivity alternations (dative/accusative alternations) in Spanish. As for the first phenomenon, and more concretely the purported existence in Spanish of something comparable to the English dative alternation, we will show the weaknesses of what we consider an analysis fruit of the tendency consisting of finding in the Romance area an exact reflex of English facts. Therefore, we will refute the hypothesis defended by several authors (Masullo 1992, Demonte 1995, Romero 1997, Cuervo 2003a,b) according to which Spanish ditransitive constructions with dative clitic doubling correspond to double object constructions (DOC), whereas non-doubled constructions correspond to the so-called prepositional constructions (PC), or to-dative, in English. After a careful and exhaustive examination of the data, we will argue that Spanish (and Catalan) ditransitive constructions instantiate DOC, whether they bear clitic doubling or not. Pronominalization facts in Catalan, a language which preserves prepositional clitics, will support this analysis, based on the postulation of an affectedness/possession restriction with gradual implementation. As for the second phenomenon of study, the existence of true case alternations in Spanish, we will argue that we are dealing with a kind of variation constrained by the same restriction (or a version of it) which acts in the realm of ditransitive predicates. Here, also, Catalan data will reveal crucial for our analysis. Crucially, we will show that what lies behind Spanish and Catalan dative/accusative alternation is an instance of Differential Indirect Object Marking (DIOM